Study of K- Hsu Structure in Generalized Almost Contact Manifold (International Journal of Emerging Trends in Science and Technology, 2017)
Cartesian product of two manifolds has been defined and studied by Pandey[2]. In this paper wehave taken Cartesian product of k-Hsu-Structure manifolds, where k is some finite integer, and studiedsome properties of curvature and Ricci tensor of such a product manifold.